1985
DOI: 10.1111/j.1574-6968.1985.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid and lipopolysaccharide normal and hydroxy fatty acids as potential signatures for methane-oxidizing bacteria

Abstract: The extractable ester‐linked and the lipopolysaccharide (LPS) normal and hydroxy fatty acids of the methylotrophic bacteria Methylosinus trichosporium 0B3B, Methylobacterium organophilum XX, grown on methane and methanol, Mb. organophilum RG and Methylomonas sp. were analysed by capillary gas chromotography‐mass spectrometry (GC‐MS). Precise monounsaturated double bond position and geometry was determined by GC‐MS analysis of the derivatized fatty acids. The three species were readily distinguished based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 36 publications
5
63
0
Order By: Relevance
“…The biomarker 16:1x5c is associated with AMF (Olsson et al 1995) and also with Type I methanotrophic bacteria (Nichols et al 1985;Holmes et al 1999) and Gram ()) bacteria (White et al 1996). We confirmed that both goatgrass and starthistle are colonized by AMF in our sites (data not shown).…”
Section: Arbuscular Mycorrhizal Fungisupporting
confidence: 93%
“…The biomarker 16:1x5c is associated with AMF (Olsson et al 1995) and also with Type I methanotrophic bacteria (Nichols et al 1985;Holmes et al 1999) and Gram ()) bacteria (White et al 1996). We confirmed that both goatgrass and starthistle are colonized by AMF in our sites (data not shown).…”
Section: Arbuscular Mycorrhizal Fungisupporting
confidence: 93%
“…As with Axis 1, factors influencing these PLFA were not revealed in the CCA. The PLFA 18:1 x7t has been associated with gram-negative bacteria (Hurst et al, 1996), Psuedomonas putida (Heipieper et al, 1992) and methane oxidizing bacteria (Nichols et al, 1985). The PLFA 16:1 x5c did not have an important loading score in this analysis.…”
Section: Soil Microbial Community Composition; Plfa Analysismentioning
confidence: 88%
“…The reported AM fungal marker 16:1 x5c was not an important loading score in this analysis, and thus does not appear to have high specificity as an AM fungal marker in this soil. This PLFA is also present in many gram-negative bacteria and type 1 methanotrophs (Nichols et al, 1985;Olsson et al, 1995); therefore, its use as a specific indicator of AM fungi in soil (not roots), needs to be considered carefully.…”
Section: Ergosterol Microbial Biomass and Plfamentioning
confidence: 99%
“…Whole cells and debris were removed by centrifuging twice at 5,000 × g for 10 min, and the total membranes were pelleted from the resulting supernatant by centrifugation at 26,000 × g for 1 h. The pellet was resuspended in buffer containing 5 mM MgCl 2 and 2% (v/v) Triton X-100 (Sigma). The suspension was stirred at room temperature for 1 h, and insoluble material was collected by centrifugation at 100,000 × g for 1 h. β-Hydroxy palmitic acid in the membrane preparations was measured by gas chromatography/mass spectrometry essentially as described by Nichols et al (1985). Nonadecanoic acid methyl ester was used as the internal standard.…”
Section: Methodsmentioning
confidence: 99%